A Study on the Application of Blended Teaching to English Reading Course under the Background of Artificial Intelligence. Issue 1 (March 2021) - Zhao, Xiaoying; Yang, Yanjun
Abstract: The development of artificial intelligence technology brings a lot of benefits to various fields, including education. This paper discusses how artificial intelligence leads to the opportunity to improve learning processes and develop innovative approaches to education like blended teaching. Based on that, the author tries to provide tentative suggestions on the application of blended teaching to English reading courses with the help of artificial intelligence technology, in the hope of improving teaching and learning quality of this course, benefiting both teachers and students.